About Empty Synagogues and Jewish Communities in Today’s Romania - Badrus, Nadia (Review of ecumenical studies, 2021)
Sciendo provides publishing services and solutions to academic and professional organizations and individual authors. We publish journals, books, conference proceedings and a variety of other publications.